Epigenome-wide data collection in a case of gliofibroma - Behling, Felix; Hennersdorf, Florian; Schittenhelm, Jens (Folia Neuropathologica, 2021)
Gliofibroma is a rare tumour entity with glial and mesenchymal histological features. We describe the case of a 30-year-old woman who presented with a short history of intermittent left-sided facial pain and paraesthesia of the left upper extremity. Histologically, the tumour consisted of a mixture of glial fibrillary acidic protein (GFAP)-positive glial cells and collagen-rich stroma. Immunohistochemical and molecular analysis showed no IDH1/2, BRAF, H3F3A mutations or ATP-dependent helicase (ATRX) loss in this tumour. Illumina Infinium HumanMethylation450 BeadChip array (HM450) methylation profile of the tumour was different from typical glioma entities. Genome-wide DNA copy number analysis showed partial loss of chromosome 3 and 8. All previous cases are reviewed. Our data support the classification of gliofibroma as a rare, but distinct brain tumour entity with good prognosis.